An Analysis of Deixis in Selected Songs by Taylor Swift: A Descriptive Qualitative Study - Janah, Gita Amanda Nur; Sema, Evania; Agus, Cecep (Universitas Pamulang, 2024)
This research focuses on analyzing deixis in Taylor swift songs, including these three songs: “I Can Do It With Broken Heart,” ‘All Too Well,’ and ‘Mr. Perfectly Fine’. It has a background of deixis preventions in lyrics and conveys meaning and emotion. The main purpose is to analyze and classify the types of deixis in the lyrics and explore the meaning of the pragmatic context. The research method used focuses on descriptive qualitative on personal, special, temporal, social, and discourse deixis. This research is subjected to the content of Taylor Swift's song lyrics that have been mentioned. Data collection includes searching for Taylor Swift's song, collecting song lyrics then analyzing each deixis that appears and categorizing each deixis into the five types. Finally, interpreting the meaning of the song in its contextual form. This research shows the dominance of personal deixis with 106 first-person pronouns, 69 second-person pronouns, and 27 third-person pronouns. Furthermore, social deixis appears 38 times, spatial deixis appears 14 times, temporal deixis 9 times, and discourse deixis 3 times. This research found Taylor Swift's song tendency to use personal pronouns to express emotions in her song lyrics. The results of this study have implications for understanding the linguistic strategies used in popular songs to capture listeners' attention and convey complex emotional narratives. This research also contributes to the broader field of pragmatics by demonstrating the applicability of deixis analysis in song lyrics, potentially informing future research in linguistic analysis of song lyrics and discourse.